The principles and priorities of Dr T.D. Greenlees, medical superintendent of the Grahamstown Lunatic Asylum, 1890-1907 (Historia, 2021)
By exploring the significant role played by the medical superintendents of lunatic asylums, there is a possibility of enriching our understanding and appreciation of the varieties of asylum culture. Said differently, by investigating the tenure of a superintendent, it is possible to highlight how the individual constructed an asylum to embody a set of goals and principles. Along these lines, the study aims to explore and investigate the Grahamstown Lunatic Asylum, under the medical superintendence of Dr Thomas Duncan Greenlees from 1890 to 1907. In order to explore Greenlees's priorities and primary topics, the asylum's annual reports provide a valuable resource. From the close examination of the annual reports several key topics emerge. The examination of the topics is informed by recent scholarship on moral therapy and Michel Foucault's analysis of power.  Die bestudering van die beduidende rol wat mediese superintendente speel in sielsiekegestige kan ons begrip van en waardering vir die verskillende vorms van inrigtingkultuur verryk. Deur die ampstermyn van 'n superintendent te ondersoek, kan vasgestel word hoe dié persoon 'n inrigting opbou om 'n stel oogmerke en beginsels te beliggaam. Op hierdie grondslag beoog die studie 'n verkenning van en ondersoek na die Grahamstown Lunatic Asylum onder dr Thomas Duncan Greenlees as mediese superintendent van 1890 tot 1907. Die inrigting se jaarverslae bied 'n waardevolle bron vir die verkenning van Greenlees se prioriteite en primêre onderwerpe. By nadere ondersoek van die jaarverslae kom verskeie belangrike onderwerpe na vore. Die bestudering van hierdie onderwerpe geskied aan die hand van onlangse navorsing oor morele terapie en Michel Foucault se ontleding van mag.
Keywords: Lunatic asylums; Morele terapie; Sielsiekegestige; Thomas Duncan Greenlees; Michel Foucault